Alum Section Revitalization: Analysis and Redesign of SMK Telkom Bandung Website using Goal-Directed Design - Adrianto, Rexcy Putra; Sardi, Indra Lukmana; Saputra, Wahyu Nur (eProceedings of Engineering, 2025)
This study addresses the usability challenges of the alumnimanagement system at SMK Telkom Bandung by redesigningthe platform using the Goal-Directed Design (GDD)methodology. The existing system faced critical issues,including fragmented alumni information, poor interfacedesign, and inefficient manual administrative processes.Through interviews and observations with 30 participants—including students, alumni, parents, and administrativestaff—this research identified key pain points and user needs.The modeling phase developed user personas, goals, mentalmodels, and interaction models to inform the design process.The requirements phase mapped user goals to systemfeatures, which guided the creation of a conceptual model andwireframes during the framework phase.The redesigned alumni platform was evaluated using theSystem Usability Scale (SUS) with 18 participants. The resultsshowed a significant improvement in usability, with the SUSscore increasing from 58.06 to 82.92, surpassing the industrystandard of 68. The new platform resolved key pain points byintroducing a centralized testimonial repository, an alumnidistribution map, and an automated job posting system.Additionally, the administrative dashboard streamlined datavalidation workflows, reducing manual workload andimproving operational efficiency.This research demonstrates how Goal-Directed Designeffectively aligns system functionalities with user needs,resulting in measurable usability improvements. The studyconcludes that the redesigned platform enhances userengagement, optimizes administrative processes, and deliversa more intuitive and efficient alumni management system.Future work is recommended to further refine the job searchfiltering system, improve submission feedback mechanisms,and expand usability testing to a broader user base.Keywords: Alumni Portal, Usability Testing, Goal-DirectedDesign, System Usability Scale, User Experience, WebRedesign, Educational Technology